2015
DOI: 10.1111/nmo.12693
|View full text |Cite
|
Sign up to set email alerts
|

Auricular vagal nerve stimulation ameliorates burn‐induced gastric dysmotility via sympathetic‐COX‐2 pathways in rats

Abstract: BACKGROUND & AIMS Severe burn injury has been demonstrated to delay gastric emptying. The aim of this study was to investigate effects and cellular mechanisms of auricular electroacupuncture (AEA) at the acupoints innervated by the auricular branch of vagus nerve (ABVN) on burn-induced gastric dysmotility in rats. METHODS Propranolol (β-adrenoceptor antagonist) was injected intraperitoneally after the rats underwent burn injury. All experiments were performed six hours following burn/sham burn injury. AEA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
(75 reference statements)
3
17
0
Order By: Relevance
“…In the current study we found that “FD” rats showed an elevated plasma NE level that was further increased with under RD; both of these were suppressed with EA. This was consistent with the former study investigating the effect of EA on impaired gastric motility induced by burn injury . Together with the data of HRV, our findings have strongly demonstrated that the ameliorating effect of TEA on gastric slow waves was mediated via the autonomic mechanisms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study we found that “FD” rats showed an elevated plasma NE level that was further increased with under RD; both of these were suppressed with EA. This was consistent with the former study investigating the effect of EA on impaired gastric motility induced by burn injury . Together with the data of HRV, our findings have strongly demonstrated that the ameliorating effect of TEA on gastric slow waves was mediated via the autonomic mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with the former study investigating the effect of EA on impaired gastric motility induced by burn injury. 59 Together with the data of HRV, our findings have strongly demonstrated that the ameliorating effect of TEA on gastric slow waves was mediated via the autonomic mechanisms. However, it should be pointed that regarding the measurement of vagal activation, the spectral analysis of HRV and plasma PP showed inconsistent results: EA increased vagal activity based on HRV analysis but showed no effect on vagal activity based on the plasma PP.…”
Section: Discussionsupporting
confidence: 75%
“…Gastric contraction in rats resulted also in response to aVNS (Gao et al, 2007). aVNS ameliorated burn-induced gastric dysmotility and improved its emptying in rats (Li et al, 2015a). Interestingly, cardiovascular and gastric responses were abolished by blockade of vagal transmission using the muscarinic receptor blocker atropine, which highlights the involvement of VN in both responses and in aVNS (Gao et al, 2007).…”
Section: Vagus Nerve Stimulation – From Biophysics To Animal and To Hmentioning
confidence: 99%
“…The plasma noradrenaline concentration, which acts as indicator of autonomic function, has been reported to be proportional to the sympathetic activities [36]. It is documented that stimulation of the SM acupoints can improve gastric emptying and suppress the cyclooxygenase-2 (COX-2) protein expression in gastric tissues mediated via the sympathetic-COX-2 pathway [37]. Thus, the increased noradrenalin may be due to interaction between the sympathetic system and COX-2 activity.…”
Section: Resultsmentioning
confidence: 99%